Relationships between the Food Expectancy Questionnaire (FEQ) and the Food Frequency Questionnaire (FFQ) - Reid, Marie; Bunting, Jane; Hammersley, Richard (Appetite, 2005)
The outcome expectancies of 250 respondents were examined using the Food Expectancy Questionnaire (FEQ), comparing expectancies about four different foods: fruit, vegetables, chocolate and sweets and plain biscuits. These expectancies were related to diet as assessed by a Food Frequency Questionnaire. As with alcohol expectancies [Jones, B. T., Corbin, W. & Fromme, K. (2001). A review of expectancy theory and alcohol consumption. Addiction, 96, 57-72], on which this research was modelled, positive and negative outcomes were the main factors for all foods, accounting jointly for between 33 and 40% of expectancy variance in factor analysis and predicting as much as 16% of the variance in relevant food intake measures by linear regression. Expected positive and negative outcomes of eating were predominantly immediate psychological after-effects, rather than including orosensory experiences, or longer-term effects on health or well-being. Other expectancies varied from food to food. FEQ expectancies for different foods have similar factor structure and were related to self-reported diet, the FEQ therefore shows promise as a means of modelling cognitions about eating.
Keywords: Food outcome expectancies; Food Frequency Questionnaire; Food attitudes and behaviour; Psychology of eating; Eating cognitions